2021
DOI: 10.1631/fitee.2000062
|View full text |Cite
|
Sign up to set email alerts
|

Consensus of multi-agent systems with dynamic join characteristics under impulsive control

Abstract: We study how to achieve the state consensus of a whole multi-agent system after adding some new agent groups dynamically in the original multi-agent system. We analyze the feasibility of dynamically adding agent groups under different forms of network topologies that are currently common, and obtain four feasible schemes in theory, including one scheme that is the best in actual industrial production. Then, we carry out dynamic modeling of multi-agent systems for the best scheme. Impulsive control theory and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…[29] Especially in the world, the installation of LPWAN network is seriously limited due to the difficulty of accessing the backbone communication network for the equipment distributed in a wide range. Yang et al found that artificial intelligence technology system contains many devices, such as digital multimeter, standard source, controller and so on [30]. Integrating all kinds of equipment can effectively improve the intelligence and automation of artificial intelligence technology, promote the continuous development of artificial intelligence technology, and reflect the value of artificial intelligence technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[29] Especially in the world, the installation of LPWAN network is seriously limited due to the difficulty of accessing the backbone communication network for the equipment distributed in a wide range. Yang et al found that artificial intelligence technology system contains many devices, such as digital multimeter, standard source, controller and so on [30]. Integrating all kinds of equipment can effectively improve the intelligence and automation of artificial intelligence technology, promote the continuous development of artificial intelligence technology, and reflect the value of artificial intelligence technology.…”
Section: Literature Reviewmentioning
confidence: 99%